Intensive Bimanual Intervention for Children Who Have Undergone Hemispherectomy: A Pilot Study. Issue 3 (July 2021) - Robert, Maxime T.; Ferre, Claudio L.; Chin, Karen Y.; Brandao, Marina B.; Carmel, Jason; Araneda, Rodrigo; Bleyenheuft, Yannick; Friel, Kathleen; Gordon, Andrew M.
Abstract : To conduct a pilot study to assess the feasibility and effectiveness of an intensive bimanual intervention on upper limb function in children who have undergone hemispherectomy surgery. Abstract : Purpose: To conduct a pilot study to assess the feasibility and effectiveness of an intensive bimanual intervention on upper limb function in children who have undergone hemispherectomy. Methods: Thirteen children received 90 hours of intensive bimanual training (Hand-Arm Bimanual Intensive Therapy, HABIT). The Jebsen-Taylor Test of Hand Function (JTTHF), Box and Block Test (BBT), Assisting Hand Assessment (AHA), ABILHAND-Kids, and Canadian Occupational Performance Measure (COPM) were assessed by a masked clinician twice before, immediately, and 6 months after treatment. Results: Significant improvements over time were found in the JTTHF, AHA, ABILHAND-Kids, and COPM. Conclusion: Completion of HABIT was feasible for children with hemispherectomy. Improvement of bimanual function and functional goals can be related to the nature of the activities prioritized in HABIT training.